Mastery Of Sociolinguistic Concepts Of Pragmatic Skills By Junior High School Students - Yossi Pratiwi; Sridelli Dakhi (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
Abstract. Skilled in pragmatic language, means skilled in using language forms ( words, phrases and clauses appropriately according to the conditions, situations and social contexts behind it. Such pragmatic skills may be established if the situation, conditions and social context behind the use of the language can be adequately mastered. This study aims to describe the percentage of contributions to the mastery of sociolinguistic concepts with pragmatic skills. In line with the purpose of the study, sociolinguistic mastery data with pragmatic skills of 28 sample people netted with test instruments and analyzed with statistics r¬2.From the results of the analysis conducted, obtained a determination index of 0.78 which means; mastery of sociolinguistic concepts contributes 78% to the achievement of students' pragmatic skills. In accordance with the results of the above analysis, it can be concluded that mastery of sociolinguistic concepts is a variable of criteria that contributes very meaningfully to the improvement of pragmatic skills. Thus, the research hypothesis yaang said that the mastery of the concept of sociolinguistics contributes meaningfully to the development of pragmatic skills of students of SMP Negeri 1 Nias Selatan, the truth is proven